(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current situation of emergency contraceptive (EC) use among students of the University of Medicine and Pharmacy – Vietnam National University, Hanoi (UMP – VNU). Subjects and Methods: A descriptive cross-sectional study was conducted on 286 students of UMP – VNU. Data were collected through an online survey and analyzed using IBM SPSS Statistics 26. Results: Among the 286 students, 141 (49.0%) reported having had sexual intercourse, of whom 111 (78.7%) had used emergency contraception. Additionally, 21.3% had experienced unintended pregnancy. The most commonly used EC method was emergency contraceptive pills (90.9%), followed by unknown pills (8.1%) and copper intrauterine devices (0.9%). About 37.8% of students reported overusing EC pills, 59.5% were concerned about their effectiveness, and 27.9% experienced side effects. Only 39.6% of those who had used EC intended to continue using it in the future, while the majority chose not to. Conclusion: The study shows a high rate of sexual activity and emergency contraceptive use among students, with EC pills being the most commonly used method. However, there remains widespread misuse, overuse, and a lack of knowledge, contributing to a high rate of unintended pregnancies. Many students are concerned about the effectiveness and side effects of the pills.